Oryzalin-induced polyploidy in Borago officinalis reveals cell-wall remodelling via immunofluorescence microscopy - Šenkyřík, Josef Baltazar; Milewska-Hendel, Anna; Král, Daniel; Ondřej, Vladan (Frontiers in Plant Science, 2025)
IntroductionArtificial polyploidisation is a powerful biotechnological approach for improving morphological and physiological traits in medicinal plants. We investigated the consequences of chemically induced whole-genome duplication in Borago officinalis L.MethodsTetraploidy was induced in vitro using oryzalin. Flow cytometry verified the establishment of mixoploid and stable tetraploid subclones. Selected tetraploids were evaluated for morphology, anatomy, and cellular features using light/confocal microscopy and immunofluorescence labelling of pectic epitopes (homogalacturonan and rhamnogalacturonan I).ResultsRelative to diploids, tetraploids displayed thicker, darker green leaves, increased trichome density, and a distinct growth habit. Microscopy showed significantly enlarged stomata with reduced density, expanded vascular tissues, and altered mesophyll organisation. Immunofluorescence revealed distinct patterns of cell-wall remodelling in tetraploid tissues.DiscussionThese findings illuminate the structural and histochemical consequences of genome-dosage changes in B. officinalis and highlight the potential of chemically induced polyploidy to enhance agronomic and pharmaceutical traits. The work provides a platform for future applications in plant metabolic engineering and molecular pharming.